Wired to Exit: Exploring the Effects of Wayfinding Affordances in Underground Facilities Using Virtual Reality. (April 2021) - Kostakos, Panos; Alavesa, Paula; Korkiakoski, Mikko; Marques, Mario Monteiro; Lobo, Victor; Duarte, Filipe
Background: Wayfinding has been adopted in several intenseevacuation and navigation simulations ; however, the use of biometric measurements for characterizing physiological outcomes has been somewhat overlooked and applied only under limited laboratory conditions. Methods: Twenty-four participants took part in a virtual reality (VR) experiment using a wayfinding installation with the Oculus Rift S head-mounted display (HMD). They were immersed in a simulation of a burning underground parking lot and tasked to navigate to the exit. The purpose of this research was to investigate the high-level effect of wayfindingassistive lights onbehavioral, physiological, and psychological outcomes . Participants were split into two groups: the control group was exposed to a scene without assistive lights, and the experimental group was exposed to the same scene with assistive lights. Results: Results indicate there was no statistically significant difference between the groups in traveled distance, pauses, turns, or game completion time. Curiously, differences between the two groups inheart rate (HR) outcomes were found to be statistically significant, with subjects in the control group displaying an increasing HR trend during simulation. Conclusions: This finding, in accordance with previous studies that have shown the efficacy of landmarks and wayfinding affordances in reducing cognitive demands, suggests that assistive lights might contribute to improved brain wiring connectivity during the game. We discuss these findings in the context of a richwayfinding affordances literature.